Pengaruh Faktor Kebudayaan dan Faktor Pribadi terhadap Perilaku Menabung Siswa SMK Negeri 1 Negara - Komang Trilia Intayani; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
The purpose of this study is to determine the influence of cultural factors and personal factors on saving behavior. The sample technique used in this study was purposive sampling as many as 134 students. Data collection methods in this study using a questionnaire and interviews. The data analysis technique used multiple linear regression analysis through the T test and F test. The results of this study indicate that partially cultural factors and personal factors have a positive and significant effect on saving behavior with a cultural factor significance value of 0.001 and a personal factor significance value of 0.000. Simultaneously, cultural factors and personal factors have a positive and significant effect on saving behavior with a significance value of 0.000.